2011
DOI: 10.4314/ejhd.v25i1.69843
|View full text |Cite
|
Sign up to set email alerts
|

Factors predisposing to rhegmatogenous retinal detachment among Ethiopians

Abstract: Aim: To determine and describe the causes and risk factors predisposing Ethiopian patients to rhegmatogenous retinal detachment (RRD). Methods: A retrospective study of all patients with RRD seen at the retina clinic of Menilik II Hospital, Addis Ababa, from April 1999 to October 2003 was done. Charts of patients with the diagnosis of RRD were collected and data were filled on structured questionnaires and analyzed using EPI INFO 6 software. Results: Data were available for 276 patients (305 eyes) in whom the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
8
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 10 publications
14
8
1
Order By: Relevance
“…This is in agreement with other studies in developing nations which showed that ocular trauma was a risk factor for 20.7%-30% of RRD cases [9,13]. …”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…This is in agreement with other studies in developing nations which showed that ocular trauma was a risk factor for 20.7%-30% of RRD cases [9,13]. …”
Section: Discussionsupporting
confidence: 93%
“…A retrospective descriptive study on patients with RD at Retina Clinic of Menelik II Hospital in Addis Ababa from April 1999 to October 2003 (4 years and six months period) showed that there were 305 patients with a diagnosis of RRD [13]. This is estimated to be on average 68 patients in six month period and this is comparable to our finding.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations